2021
DOI: 10.3390/ani11061609
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Extract and Probiotic Supplementation Alleviate Copper-Induced Nephrotoxicity via Modulating Oxidative Stress, Inflammation, and Apoptosis in Broiler Chickens

Abstract: The present study aimed to assess the potential protective effects of cinnamon (Cinnamomum zeylanicum, Cin) and probiotic against CuSO4-induced nephrotoxicity in broiler chickens. One-day-old Cobb chicks were assigned into seven groups (15 birds/group): control group, fed basal diet; Cin group, fed the basal diet mixed with Cin (200 mg/kg); PR group, receiving PR (1 g/4 L water); Cu group, fed the basal diets mixed with CuSO4 (300 mg/kg); Cu + Cin group; Cu + PR group; and Cu + Cin + PR group. All treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Biochemical indices in blood reflect the health and metabolic status of animals. Creatinine and uric acid are nitrogenous and proteinaceous end products of catabolic processes excreted by the kidneys and are reliable indicators of renal function [ 47 ]. When the kidneys are damaged, the levels of creatinine and uric acid in the blood rise significantly [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical indices in blood reflect the health and metabolic status of animals. Creatinine and uric acid are nitrogenous and proteinaceous end products of catabolic processes excreted by the kidneys and are reliable indicators of renal function [ 47 ]. When the kidneys are damaged, the levels of creatinine and uric acid in the blood rise significantly [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Former studies showed that hepatic Cu retention increased with dietary Cu supplementation (Kim and Kil, 2015;Wu et al, 2020). Another study employed in chickens indicated that the amount of Cu in the kidney increased somewhat as the amount of time exposed to Cu increased (Elazab et al, 2021). Interestingly, the supplementation with SeY conferred a significant antagonistic action against hepatorenal Cu accumulation in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Since the kidney is the leading platform for the excretion of Cu, the renal tubules are vulnerable to Cu harm (Elazab et al, 2021). The analysis of renal function tests unveiled momentous upsurges in serum levels of urea and creatinine in CuSO 4intoxicated birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood biochemical indices usually reflect the physiological and metabolic status of animals. Creatinine, urea, and uric acid are widely acknowledged as reliable indicators for kidney function, as they are nitrogenous and protein end products of a catabolic process that are generally excreted by the kidney [ 36 ]. Elevated concentration of these plasma indices indicate kidney damage while decreasing their concentration helps to reduce the development of kidney disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%